(untitled) (GEOMATE Journal, 2018)
Mobile and rapidly assembled structures play an important role in building temporary and semipermanent accommodations and shelters in post-disaster management. One of the most efficient construction systems that can be used in rapidly assembled buildings is lightweight panelized systems. Use of rapidly assembled panelized systems is becoming very popular for cutting the construction time and transportation costs that make them suitable options for rapid assembly construction. In addition, when acoustic and thermal insulation of buildings is important, foam filled composite sandwich panels are an effective solution. Soft, semi-rigid and rigid Polyurethane (PU) foams, which are first introduced into the market in the 1950s, are most popular types of foams. Regarding the research performed in the last decade, the structural behavior of PU foam filled sandwich panels has been investigated by several researchers worldwide. There is a need for a comprehensive feasibility studies on the use of rigid PU foam in structural sandwich panel cores so that various aspects of this material is deeply investigated. In this paper, a feasibility study carried out on a commercial type of rigid PU foam with trading name AUW763, to be used as the core material of sandwich panels, based on ASTM E1730-15. Results show AUW763 meets the standards requirements and specifications for building constructions.